2019
DOI: 10.3389/fmicb.2019.00150
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Antibacterial Mode of Action of Alpha-Mangostin on Staphylococcus epidermidis RP62A Through an Integrated Transcriptomic and Proteomic Approach

Abstract: Background: Alpha-mangostin (α-MG) is a natural xanthone reported to exhibit rapid bactericidal activity against Gram-positive bacteria, and may therefore have potential clinical application in healthcare sectors. This study sought to identify the impact of α-MG on Staphylococcus epidermidis RP62A through integrated advanced omic technologies.Methods: S. epidermidis was challenged with sub-MIC (0.875 μg/ml) of α-MG at various time points and the differential expression pattern of genes/proteins were analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Its pharmacological activities are diverse: antibacterial, anti-allergic, anti-fungal, anti-inflammatory activity, antioxidant and anticancer. [1][2][3][4][5] Previous studies demonstrated that α-mangostin can act against cancer cells via multiple pathways, [38][39][40][41] including inhibiting fatty acid synthase, signalling human epidermal growth factor receptor 2 (HER2)/phosphatidylinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 6,42 Notwithstanding its excellent bioactivity, αmangostin has limited solubility in water (2.03 x 10 −4 mg/ L at 25ºC).…”
Section: α-Mangostinmentioning
confidence: 99%
See 1 more Smart Citation
“…Its pharmacological activities are diverse: antibacterial, anti-allergic, anti-fungal, anti-inflammatory activity, antioxidant and anticancer. [1][2][3][4][5] Previous studies demonstrated that α-mangostin can act against cancer cells via multiple pathways, [38][39][40][41] including inhibiting fatty acid synthase, signalling human epidermal growth factor receptor 2 (HER2)/phosphatidylinositide 3-kinase (PI3K)/Akt and mitogen-activated protein kinase (MAPK). 6,42 Notwithstanding its excellent bioactivity, αmangostin has limited solubility in water (2.03 x 10 −4 mg/ L at 25ºC).…”
Section: α-Mangostinmentioning
confidence: 99%
“…α-Mangostin, a xanthone derivative compound isolated from Garcinia mangostana L. peel extract, has myriad pharmacological effects: antibacterial, antifungal, anti-inflammatory, antiallergic, antioxidant and anticancer activities. [1][2][3][4][5] The anticancer activity indicates that α-mangostin might serve as a potent anticancer agent in lung, stomach, colon, cervical, pancreatic, prostate, mammary gland, chondrosarcoma, renal, skin, tongue mucoepidermoid and breast cancers. [6][7][8][9][10][11][12][13][14][15][16][17][18] However, αmangostin has low solubility in water (2.03 x 10 −4 mg/L at 25ºC), and many efforts have been made to improve it: structure modification, co-solvation, solid dispersion, emulsion, complexation and nanoparticle drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…The down-regulated fused signal recognition particle receptor (ftsY [SE0910]) is part of the S. epidermidis Sec secretion system, and is involved in cell division, as a highly energy demanding process. The expression of ftsY was also reduced when S. epidermidis cells were exposed to α-mangostin, a natural xanthone with antimicrobial activity [28]. This indicates another energy saving process as an adaptation response.…”
Section: Response Mechanisms To Ddac Of the Ddac-adapted S Epidermidmentioning
confidence: 92%
“…Similarly, S. epidermidis did not develop resistance towards 2 despite continuous exposure at 0.38-3.05 μM across 19 passages in both planktonic and biofilm cells (Sivaranjani et al, 2017). A later study conducted by Sivaranjani et al (2019) revealed molecular antibacterial mechanisms of 2 on S. epidermidis by downregulating the expression of genes responsible for bacterial cytoplasmic membrane integrity, cell division, teichoic acid and fatty acid biosynthesis, as well as DNA replication and repair systems. The target on multiple metabolic pathways by 2 minimized the risk of resistance development which greatly increased the potential of the xanthone as anti-bacterial agents for acne treatment.…”
Section: Antibacterial Activity Of Xanthones For Acne Treatmentmentioning
confidence: 97%